Bone Development and Disease in Infants (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Children’s bone growth is continuous, and remodelling is always extensive. Growth proceeds from a vulnerable part of the bone, the growth plate. In remodelling, old bone tissue is gradually replaced by new tissue. Many bone disorders arise from the changes that occur in a growing child’s musculoskeletal system, and these disorders can positively or negatively impact bone development. Other bone disorders may be inherited or occur in childhood for unknown reasons.Bone disorders in children can result from factors that affect people of all ages, including injury, infection (osteomyelitis), cancer, and metabolic diseases. Causes of bone disorders can involve the gradual misalignment of bones and stress on growth plates during growth. Congenital deformities such as clubfoot or developmental dysplasia of the hip can lead to important alterations of bone development, causing severe dysfunction. Certain rare connective tissue disorders can also affect the bones, such as Marfan syndrome, osteogenesis imperfecta, and osteochondrodysplasias.Many specialists are involved in the management of bone development disorders in children and adolescents, such as neurosurgeons, plastic surgeons, general surgeons, ORL surgeons, maxillofacial surgeons, orthopaedics, radiologists, and pediatric intensive care physicians.The aim of this Special Issue is to present the latest research on the etiology, physiopathology, diagnosis and screening, management, and rehabilitation related to bone development and disease in infants, focusing on congenital, developmental, post-traumatic, and post-infective disorders.